MORPHOPHONOLOGICAL BEHAVIOR OF -ize AND -ify SUFFIXATION IN ENGLISH VERBAL DERIVATION: A CORPUS-BASED STUDY - Abd Jabar; Zeny Luthvia; Diska Fatima Virgiyanti; Ervin Yudianto; Alif Cahya Setiyadi; Moses James Olenyo Malande (International Journal of English Learning and Applied Linguistics (IJELAL), 2026)
This study examines the morphophonological behavior of the English derivational suffixes -ize and -ify, focusing on their influence on primary stress placement in derived verbs. Using a descriptive corpus-based approach, the study analyzes English words ending in -ize and -ify retrieved from Sketch Engine, with phonetic transcription and stress placement verified through Oxford dictionary entries. The data were classified based on suffix type, base form, derived form, and the phonetic transcription of both the base and suffixed forms. The findings show that -ize is largely stress-neutral, as most derived verbs preserve the stress pattern of their base forms. By contrast, -ify tends to be more stress-sensitive, frequently leading to stress reassignment toward the antepenultimate syllable. Although the two suffixes differ in their degree of stress sensitivity, both display a strong tendency toward antepenultimate stress in derived verbs. The study also identifies several irregular patterns, indicating that stress placement in English derivation is shaped not only by suffixation but also by lexical, prosodic, and historical factors. These findings underline the close interaction between morphology and phonology in English word formation and offer useful implications for pronunciation instruction and morphological awareness in English Language Teaching.